Labour, employment and economic growth in India - Ramaswamy, K. V. (Cambridge : Cambridge University Press, 2015)
Productive employment opportunities constitute the primary ingredient of economic transformation and inclusive growth. This volume examines India's development experience in the sphere of labour, employment, structural change and institutional challenges in the recent past. The contributors have extended the boundaries of contemporary debate in a variety of ways by undertaking fairly detailed empirical analysis of selected aspects of growth and employment change in India. They uncover the recent patterns of change, between and within sectors over time that challenges popular beliefs and understanding of employment growth in India. Analysis of population ageing, gender discrimination, impact of labour regulation; institutional analysis; dynamics of judicial interpretation of laws protecting workers in the years of economic liberalisation among others have enriched the content. The volume contributes to our knowledge of India's labour market and sheds light on employment challenges in an economy undergoing rapid growth and economic transformation.
Economic growth and employment -- Introduction and review of issues / 1.K.V.Ramaswamy -- India's labour market during the 2000s / Jayan Jose Thomas -- Services-led growth and employment in India / Ajit Ghose -- Growth,structural change and poverty reduction : evidence from India / Rana Hasan, Sneha Lamba and Abhijit Sengupta -- Age structure transition, population ageing and economic growth : new evidence from India / M.R.Narayana -- Labour intensity in Indian manufacturing : measurement, patterns and determinants / Deb Kusum Das,Kunal Sen and Pilu Chandra Das -- Gender discrimination in manufacturing employment in India, 1999-2009 / B.N.Goldar and Suresh Aggarwal -- Employment and labour law -- From rigidity to flexibility : changes in the Indian labour market / Bibhas Saha -- Employment protection legislation and threshold effects / K.V.Ramaswamy -- Who is a worker? : searching the theory of the firm for answers / Jaivir Singh -- Labour jurisprudence of the supreme court : recent trends / Ramapriya Gopalakrishnan -- Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Labor supply -- India; Labor market -- India; Economic development -- India